Peningkatan Motorik Halus Anak Usia Dini melalui Pemanfaatan Media Daun dalam Kegiatan Pembelajaran - Rifka R Sidabutar; Hasnah Siahaan (Institut Agama Islam Negeri Langsa, 2019)
Early childhood has a range of abilities that need to be developed, one of them is fine motor capability, which is organizing the use of small muscles such as fingers and hands that often require care and eye coordination by hand. In the development of fine motor ability of the child that appears in the number of children who reach the end, where the research subject consists of 20 children, 8 boys and 12 daughters. Cycle I is only 10 children (40%), cycle II to 18 children (90%) That are categorized quite well on the II cycle. Based on the results obtained, it can be concluded that the implementation of action, observation, and reflection. The data of this research includes qualitative data that the utilization of natural media made from Based on the results of the research, it is recommended to early childhood teachers to apply natural-made leaves in the development of child fine motor skills. Thereby improving the fine motor of early childhood through the use of the media in the surrounding leaves is very effective to be used in learning.